Penguatan Keterampilan Menulis Insya Melalui Pembelajaran Idiom Bahasa Arab bagi Mahasiswa Pendidikan Bahasa Arab - Zulaeha, Zulaeha; Trisnawati, Ira; Ishak, Awal Jumaidil (Al-TA'DIB: Jurnal Kajian Ilmu Kependidikan, 2023)
The purpose of this research is to investigate students’ statistical literacy in terms of their basic knowledge of mathematics. This descriptive study involved the population of grade IX students totaling 264 students from 9 classes in a junior high school. Applying cluster random sampling technique using the Slovin formula, a sample of 65 students from 3 classes was obtained. Data was collected through multiple-choice tests to measure basic knowledge of mathematics and essay tests to measure students' statistical literacy skills. The results of this study reveal that students with high basic mathematical knowledge are able to achieve indicators of presenting data and interpreting data, students with basic knowledge of moderate mathematics are able to achieve indicators of interpreting data, and students with low basic knowledge of mathematics were not been able to achieve all indicators of statistical literacy ability.Keywords: basic knowledge of mathematics; statistical literacy